Improving Teenagers’ Divergent Thinking With Improvisational Theater - Hainselin, Mathieu; Aubry, Alexandre; Bourdin, Béatrice (Frontiers in Psychology, 2018)
Improvisational theatre (improv) is supposed to have an impact on cognitive processes (divergent thinking, flexibility, language, memory, problem solving, and co-construction), academic performance, and everyday life in many ways. However, little research studied on the psychological impact of improv, with some results highlighting a divergent thinking enhancement in children and adults, but not with teenagers, one of the most important age groups to practice improv. Therefore, this study aims to assess divergent thinking for middle school students before and after an 11-week session compared to a control group with a sport practice. The Alternative Uses Task was used before and after the session for both groups to evaluate divergent thinking. The improv group had better performance in originality, flexibility and gave less prototypical items after the improv sessions compared to before, while the control group performance was similar before and after. Our results suggest that improv helps teenagers’ divergent thinking to improve, not only with experimental games in the lab context but also after ecological sessions. We urge scientists to study in depth psychological impacts of improvisational theatre and applied improvisation, for a better understanding of improv and as a model to study embodied cognition.